Enhancing Professionalism Through Counselling in Public Universities in Edo and Delta States of Nigeria - Augustina Izehiuw, Efosa-Ehioghiren; Atinuke Titilope, Babalola (Manunggal Halim Jaya, 2024)
This study investigated enhancing professionalism through counselling in public universities in Edo and Delta States of Nigeria. The purpose of the study was to find out if professionalism predicts counsellor competencies of prospective counsellor in public Universities in Edo and Delta States. Two research questions were raised and one hypothesis was formulated and tested at 0.05 level of significance. Survey research design adopting the correlational approach was used in this study. The population of the study comprised all Masters Students in public universities in Edo and Delta States in the 2020/2021,2021/2022 and 2022/2023 sessions who had completed practicum counselling course. A sample of 89 prospective counsellors was used for the study. Reliability coefficients of 0.914, 0.630,0.818, 0.691, 0.607, were obtained for competence and skill, communication, teamwork, critical thinking, ethics respectively for the Counsellor Personality characteristics questionnaire subscale. 0.810, 0.896, 0.796 were obtained for knowledge, skills and behavioural sub-scales respectively for Counsellor Competency Questionnaire. Descriptive statistics and Regression analysis were used for analysis of data and testing of hypothesis respectively. The outcomes of the study revealed the following: The level of counselling competencies of prospective counsellors in public universities in Edo and Delta States is high; The five points professionalism do not significantly predict Counselling Competencies. It was recommended among other that professional counsellors should concentrate on the training programme of the prospective counsellors in order to inculcate in students the techniques and ethics of the profession since it has been proven that the five points professionalism do not predict counselling competencies.